The Effect of Motor and Cognitive Experiences on Mental Rotation Ability in Boys - Jalal Dehghanizade; Hasan Mohamadzade; Hadi Moradi (University of Tehran, 2015)
Mental rotation is the ability to imagine how an object will look if rotated away from the orientation in comparison with the one which is actually presented. That is a component of spatial abilities. This research aimed at comparing mental rotation ability in those with motor and cognitive experiences. The method of this research was causal-comparative and the sample was selected purposively. The sample included 60 boys with a mean age of 17.17 years (motor experience = 20 subjects in wrestling group, cognitive experience = 20 subjects in computer game group and without motor and cognitive experiences (control) = 20 subjects). Peters et al. Mental Rotation Test (version A) (1995) was used to compare mental rotation. The results of the one-way ANOVA test showed a significant difference between the control group and wrestling group and also between the control group and PC game group (P≤0.01). There was no significant difference between wrestling and PC game groups in mental rotation (P>0.05). These findings indicated the positive effects of motor and cognitive experiences on cognitive development (mental rotation).